Analysis of the Selection and Installation of a Pump for an Overflow Swimming Pool with a Volume of 67 Cubic Meters - Achmad Wibolo; I Ketut Suherman; I Dewa Made Pancarana; I Ketut Adi (Logic : Jurnal Rancang Bangun dan Teknologi, 2023)
In the swimming pool there is a pump system that is useful for circulating water. Pumps  in  swimming pools can affect water quality. Dirty  water will be cleaned by the  filter  and  will  be re-circulated to the swimming pool. The calculations  that  must  be  known  are  the  volume  of  the swimming  pool,  pump  power, flow rate, and the curve of  the pump. In  order  for  the  selection of a swimming  pool pump  to be  appropriate, the  correct  calculation  must  be made  so that the pump  can provide  the best  performance for a swimming pool with a volume of 67 cubic meters  and is able to circulate swimming pool water 4 times  during 12 working hours.